IMPROVING STUDENTS’ ENGLISH PRONUNCIATION SKILL THROUGH AUDIO-LINGUAL METHOD - Yani Octafia (JEELL (Journal of English Education, Linguistics and Literature), 2025)
This research  aims to find and analyze the difficulties in  English pronunciation English  on students of English department. In improving the variety of English teaching methods, especially learning methods that can encourage students to improve their ability to pronounce every word in English fluently in order to create effective communication situations. The  writer  used  the  descriptive  qualitative  method.  The  participant of  this research  was  second  semester  students  of  English  Department  of  Universitas Pamulang in  the  Academic  Year  2024/2025.  There were  10  respondents  chosen  randomly.  The  data  of  this  research were  taken  from written  test  through  pre test and post test about identifying phonemic consonants and symbols in English Words by giving test. The  writer  used 40 tests  to  analyze  by  students.  Moreover,  the  writer  only  focused  on  analyzing  the  statement sentences The Audio-Lingual (AL) approach is a method of learning English that focuses on developing speaking and listening skills. The techniques used in the audio-lingual approach are:  Focus on pronunciation, use of audio, and drills and exercises.